Biopharmacological considerations for accelerating drug development of deguelin, a rotenoid with potent chemotherapeutic and chemopreventive potential. Issue 11 (1st April 2019) - Varughese, Rahel Sarah; Lam, Walter Sze‐Tung; Marican, Ahmad Abdurrahman bin Hanifah; Viganeshwari, S. Hema; Bhave, Anuja Satish; Syn, Nicholas L.; Wang, Jigang; Wong, Andrea Li‐Ann; Kumar, Alan Prem; Lobie, Peter E.; Lee, Soo Chin; Sethi, Gautam; et al.
Abstract : Deguelin is a rotenoid compound that exists in abundant quantities in the bark, roots, and leaves of the Leguminosae family of plants. An analysis of evidence from both in vitro and in vivo studies suggests that deguelin displays potent anticancer activity against multiple cancer types and exhibits chemopreventive potential in Akt‐inducible transgenic mouse models. Deguelin appears to impede carcinogenesis by enhancing cell apoptosis and hindering malignant transformation and tumor cell propagation. Crucial oncogenic pathways likely targeted by deguelin include the epithelial‐to‐mesenchymal transition; angiogenesis‐related pathways; and the phosphoinositide 3‐kinase/Akt, Wnt, epidermal growth factor receptor, c‐Met, and hedgehog signal transduction cascades. This review article provides a comprehensive summary of current preclinical research featuring deguelin as a leading chemotherapeutic and chemopreventive compound, and it highlights the importance of identifying companion molecular biomarkers and performing systemic pharmacokinetic studies for accelerating the process of developing deguelin as a clinical anticancer agent. Abstract : Deguelin can modulate various key hallmarks of cancer initiation, promotion, and progression, as well as alter the activation/expression of various oncogenic molecules in tumor cells. It is also shown to exhibit significant chemopreventive and therapeutic effects in different cancer mouse models.